Developing Visual Prompt Video of Canva for Students’ Speaking Performance at Rumah Belajar Saab Shares 09 Nias Utara - Febri Yanti Zendrato; Afore Tahir Harefa; Hidayati Daeli; Kristof Martin Efori Telaumbanua (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2024)
This study aims to develop visual prompts in the form of videos using the Research and Development (R&D) approach with the 4D development model (Define, Design, Develop, Disseminate). The use of visual prompts in videos aims to improve learning effectiveness and facilitate user understanding. At the Define stage, a needs analysis and problem identification were conducted to determine the objectives and content of the video. At the Design stage, video scenarios and designs are developed by considering visual elements and messages to be conveyed. The Develop stage involves creating video prototypes using supporting technology and software, namely the Canva application, as well as initial testing to obtain feedback. Finally, the Disseminate stage involved video distribution and end-user evaluation to measure the success of the development. The results showed that the visual prompt video was able to significantly increase students’ engagement and comprehension, thus having a positive impact to the increasing speaking performance in learning process